Chemical Composition and Nutritive Value of Brachiari paspaloides - Rawat, G.S.; Tiwari, V.K.; Ojha, A.C. (Asian Journal of Chemistry, 2010)
Ether extract, total ash and concentration of nutrients such as protein, Ca, Mg, K, P, Fe, crude fibre and calorific value of Brachiari paspaloides in three growing stages and in different plant parts were determined. Free amino acids, sugars, hexoses, pentoses and total sugars were also studied. It was found that flowering stage is more nutritious than pre and post flowering stage.